Iconic characters, Júlia Matos and Jade El Adib and the importance of their characterizations: Costumes, hair and makeup (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article addresses the importance of the characterization of actors/actresses in the performing arts and their specific areas: television, cinema, theater, musical shows and performances. For each area mentioned, there is a particular work of costumes, makeup and hair that need to be appropriate to the scenographic environment to which they will be presented. The scenography of the environment, the light, the type of screen (television and cinema) as well as the size of the theater or even in the case of shows where singers perform, in large stadiums need specialized professionals, competent in their functions and together, directors, lighting designers, costume designers, hairdressers, makeup artists in teams, will develop a quality and cohesive work. The case study of two soap opera characters, conceived by costume designer Marília Carneiro are in this article exemplifying some points regarding the characterization of characters.
Keywords: performing arts; costumes; makeup; hairstyles